Measuring corporate management and leadership capability - Neely, Andrew; Gray, Dina; Kennerley, Mike; Marr, Bernard (Cranfield School of Management, 2002)
The Council for Excellence in Management and Leadership commissioned the Centre for Business Performance at Cranfield School of Management to produce for them a report investigating the case for corporate reporting and disclosure in the field of organisational management and leadership. Clearly there are pros and cons for such reporting, especially if it is made compulsory through the forthcoming Company Law review, but on balance the authors are of the opinion that: 1. Greater corporate reporting and disclosure in the field of organisational management and leadership is not only desirable, but also inevitable. 2. Legislation may result in organisations reporting more in the field of organisational management and leadership sooner than they would otherwise, but in the longer term market forces will force them to report this information. 3. The steps that organisations are taking to adopt measurement frameworks that balance financial and non-financial issues mean that they are already building the infrastructure necessary to enable this reporting. 4. It is impractical to expect that a generic set of reporting standards applicable to all organisations can be developed for this area. It is widely believed that performance measures are context and strategy specific. Hence requiring organisations to report against a standard set of measures will simply result in additional bureaucratic burdens being placed on them. 5. An alternative, and much more pragmatic approach, however, is to accept that the role of measurement is to provide insight. What investors, and other external stakeholders, want is insight into the management and leadership talent pool that exists within organisations. As a result it should be possible to encourage and/or require organisations to release information in their annual reports which provides fact based insights into their management and leadership talent pool. 6. To provide a structure for such disclosure the authors recommend that a portfolio of critical questions about the management and leadership talent pool be developed and that organisations be encouraged and/or required to provide answers to these questions through fact based evidence of their own choosing. 7. Many organisations would benefit from the rigour provided by this approach. Far too often the performance measures that organisations have in place in the arena of organisational management and leadership are poorly developed and deployed.
A Report Commissioned by the Council for Excellence in Management and Leadership from the Centre for Business Performance at Cranfield School of Management